The Association Between The International Society On Thrombosis And Haemostasis- Disseminated Intravascular Coagulation Score And Early Mortality Of Acute Leukemia Patients - tantri, Anita; Dairion Gatot; Lubis, Heny Syahrini; Mardia, Andri Iskandar (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background: Disseminated Intravascular Coagulation (DIC) is a serious complication frequently found in patients with acute leukemia and is associated with increased early mortality. The ISTH-DIC score is widely used to assess the severity of DIC. However, data on the association between ISTH-DIC score and early mortality in acute leukemia patients in Indonesia remains limited. Objective: To evaluate the association between ISTH-DIC score and early mortality (≤60 days) in acute leukemia patients at H. Adam Malik General Hospital, Medan. Methods: This was a retrospective cohort study involving 68 adult patients diagnosed with acute leukemia admitted from January 2022 to June 2024. Medical records were reviewed to collect laboratory parameters (platelet count, prothrombin time [PT], fibrinogen, and D-dimer) to calculate the ISTH score. Statistical analysis was performed using bivariate and multivariate logistic regression. Results: The early mortality rate was 58.8%. A substantial proportion of patients had ISTH-DIC scores ≥5, but no statistically significant association was found between ISTH score and early mortality (p = 0.704). However, PT >1.2 seconds was significantly associated with early mortality (p < 0.001; OR 18.00). Platelet count, D-dimer, and fibrinogen levels showed no significant association. Conclusion: The ISTH-DIC score was not significantly associated with early mortality in acute leukemia patients, but individual components such as prolonged PT showed a strong correlation. Early coagulation assessment remains essential in identifying patients at risk of life-threatening complications.